UJI SITOTOKSISITAS E-GLASS FIBER REINFORCED COMPOSITE PADA SEL FIBROBLAS (METODE MTT) - , BONIFASIUS PRIMARIO, Prof. Dr. drg. Widowati Siswomihardjo, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Fiber reinforced composite has recently developed in dentistry. Addition of fiber increasing the mechanical strenght of FRC. E-glass fiber is one of fibers that commonly used because of its good strenght. Material used in medical field must accomplish the criteria of biocompatibility. The aim of this study was to evaluate the cytotoxicity of e-glass FRC on fibroblast. The materials used were E-glass fiber (R338-2400/V/P, Stick Tech Ltd., Turku, Finland) and composite resin MasterflowÂ® (Biodinamica, Brazil). There were two groups. Group one was composite resin and group two was e-glass FRC. Each material was inserted into the mold (size 2x2x25mm), then cured by visible light cure in 20 seconds, then powdered. Vero cell line (LPPT, UGM) was cultured and inserted into well with density 2x104 sel/100Î¼L, then incubated in 24 hours at 37oC (n=4). Composite resin and e-glass fiber powder that have been dissolved in culture medium then inserted into the cells and incubated. After incubation, MTT solution was added, and four hours later SDS-HCl was added. Optical density values obtained from the amount of formazan formed from ELISA plate reader with a wavelenght of 550 nm. Cytotoxicity was obtained based on cells viability relative to control group. Data was statistically analyzed by t-test. Fibroblast exposed with composite resin showed average viability at 85.65 + 0.70% and e-glass fiber was 94.83 + 6.24%. The result of t-test showed that there was significant difference between two groups (Ï<0.05). Conclusion of this experiments was e-glass FRC was not cytotoxic to fibroblast.